Analysis of Student Route Choice Model to University of Palangka Raya Using Multilogit Nomial Method - Siahaan, Neagel Banderas Zepanya; Silitonga, Sutan Parasian; Elvina, Ina (Universitas Insan Cendekia Mandiri, 2024)
The various types of routes or traffic routes that will be taken to University of Palangka Raya require route selection so that it can be efficient in distance, travel time and cost. In the selection of this road network route, route selection will be analyzed from the results of field calculations with the perceptions of road users. The data is analyzed with the help of the SPSS application so that it can be seen which routes are most attractive to students when traveling to University of Palangka Raya, factors that influence students in choosing routes to University of Palangka Raya, and characteristics of users of travel routes to University of Palangka Raya. The methods used in this research are Descriptive Method and Multilogit Nomial Method. Based on the results of research with 664 respondents, the variables that influence the selection of student routes to University of Palangka Raya between Murung Raya Dormitory, Keminting, and Yos Soedarso are distance from residence to campus, distance (dummy variable), how to travel and other reasons (dummy variable), with probability results amounting to: Pasrama = 1.1%, Pkeminting = 69.3%, Pyos soedarso = 29.7%, Plainnya = 0%.